2018
DOI: 10.1039/c8cs00169c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chemistry approaches for tuning the properties of two-dimensional transition metal dichalcogenides

Abstract: Two-dimensional (2D) semiconductors, such as ultrathin layers of transition metal dichalcogenides (TMDs), offer a unique combination of electronic, optical and mechanical properties, and hold potential to enable a host of new device applications spanning from flexible/wearable (opto)electronics to energy-harvesting and sensing technologies. A critical requirement for developing practical and reliable electronic devices based on semiconducting TMDs consists in achieving a full control over their charge-carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
239
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 233 publications
(243 citation statements)
references
References 439 publications
(567 reference statements)
2
239
1
1
Order By: Relevance
“…There are now many reports available describing how to tailor the properties of the nanosheets and parent layered materials by covalent modifications. 48,49,89,90,[102][103][104][105][106] The reactions are as diverse as the different nanosheet compositions and structures and comprise reactions with thiols, including click reactions, electrophiles, such as alkyl iodides and diazonium salts, isocyanates, epoxides and coordination with metal salts. Furthermore, with the recent focus on improving existing strategies and inventing new ones for quantitative nanosheet exfoliation, processing, and assembly, it is likely that scalable, as well as more complex photonic architectures based on 2D materials become readily available, like for example printable nanostructures and systems amenable to roll-to-roll processes.…”
Section: A Bright Future For 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are now many reports available describing how to tailor the properties of the nanosheets and parent layered materials by covalent modifications. 48,49,89,90,[102][103][104][105][106] The reactions are as diverse as the different nanosheet compositions and structures and comprise reactions with thiols, including click reactions, electrophiles, such as alkyl iodides and diazonium salts, isocyanates, epoxides and coordination with metal salts. Furthermore, with the recent focus on improving existing strategies and inventing new ones for quantitative nanosheet exfoliation, processing, and assembly, it is likely that scalable, as well as more complex photonic architectures based on 2D materials become readily available, like for example printable nanostructures and systems amenable to roll-to-roll processes.…”
Section: A Bright Future For 2d Materialsmentioning
confidence: 99%
“…40,41 The advantages for creating structural colors based on 2D materials include their tunable 2D morphology, inherent responsiveness to stimuli by swelling, diversity in composition and structure, and existence of methods to tailor and fine-tune their properties. [42][43][44][45][46][47][48][49] However, they remained almost unexplored until recent times due to the limited availability of nanosheets and efficient processing techniques for 2D materials, despite early efforts with 2D materials in thin film interference sensors. 50 With the recent advances in nanosheet processing protocols and tailoring methods, 43,[51][52][53][54] 2D materials made their way into the field of structural colors.…”
mentioning
confidence: 99%
“…However, the covalent functionalization of MoS 2 has been accomplished. [7] For example, the basal plane of the 1T-MoS 2 polytype has been reacted with organoiodides, [8] while reaction with diazonium salts has been reported for the basal plane modification of 1T [9] as well as 2H-MoS 2 . [10] Herein we adopt the recently developed method based on the addition of 1,2-dithiolanes to S-vacant sites located at the edges of exfoliated 2H-MoS 2 nanosheets.…”
mentioning
confidence: 99%
“…[14][15][16] The interfacing with molecular systems possessing tunable structures and functionalities constitutes an efficient and versatile approach to provide different charge carrier doping levels and thus to reversibly modulate the optoelectronic properties of 2DMs. [17,18] For example, it has been demonstrated that photochromic molecules, capable of undergoing reversible isomerization between two different states induced by light stimuli, [19] can serve as optically responsive components when employed to functionalize unipolar 2DMs. [20,21] Importantly, such hybrid structures take full advantage of the ultrahigh sensitivity of 2DMs to any subtle environmental change, [18] which will emerge as an additional molecular-driven photoresponsivity.…”
Section: Doi: 101002/adma201907903mentioning
confidence: 99%